Minimally Invasive Approaches in Orthognathic Surgery: A Narrative Review of Contemporary Techniques and their Clinical Outcomes - Altwaijri Abdulrahman (Wolters Kluwer Medknow Publications, 2024)
Maxillofacial surgery has evolved significantly, particularly in orthognathic procedures, shifting from invasive methods to minimally invasive techniques (MITs). Innovations, like 3D imaging, computer-aided simulations, piezoelectric surgery, and endoscopic assistance, have revolutionized patient care. These methods notably reduce bleeding, scarring, hospital stays, and recovery time, while enhancing surgical precision and outcomes. Our review focuses on modern MITs, including endoscopically assisted maxillomandibular advancement (EAMMA) and CAD/CAM technology. We conducted a thorough literature search, identifying 21 relevant articles from an initial pool of 423. The review evaluates the efficacy, complication rates, and long-term stability of these techniques, addressing challenges and future prospects. Emphasizing the significance of MI methods in orthognathic surgery, it advocates for further research and clinical adoption.